Fiscalización a la liga deportiva barrial oriental; parroquia juan Montalvo, cantón Latacunga, provincia de Cotopaxi, sector san Martín; período 2011-2012 - Tapia Tapia, Meliton Gregorio (2014)
In the present research was identified the incorrect operation of the documents which support the incomes and expenditures; this problem is given by the professional responsibility failures of the institution, further, it was detected that the purchase vouchers and sales lack the legal requirements that sustain the transactions, so do not allow them to keep control in the management of different resources, the methods what are applied to collect information were: the observation, interview, survey and the questionnaires of internal control made to the club representatives and directives of the neighborhood Sport Liga Oriental, period 2011-2012, with the aim of establishing the reasonableness and reliability of accounting information, it is determining changes strategies to overcome the deficiencies in the system and management control of economic resources through which were got important results about the accounted and audited balance. The performed audit constitutes a useful instrument for the organization in the efficient management of assets registry, originating in a certain manner a planning in the information presented by the liga.